Professional Integration of Immigrant Teachers in the School System: A literature review - Niyubahwe, Aline; Mukamurera, Joséphine; Jutras, France (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2013)
This literature review article investigates the professional integration of teachers recently immigrated to Canada and other western countries. Its findings reveal a number of obstacles to the integration of immigrant teachers into the teaching profession. The review summarizes different initiatives facilitating or hampering immigrant teachers’ access to employment and professional integration. It also notes that there is little research on teachers’ professional integration in Western French speaking countries in general, and more particularly in Quebec where these teachers are often relied upon because of the shortage of personnel in this profession.